Mechanism of morphology regulation and photocatalytic performance of bismuth tungstate by precursor pH in hydrothermal reactions - Tingting LIU; Libing CAO; Yan WU; Mengge YAN; Fanyu YANG; Zheng WU (工程科学学报)
Fluvastatin, a widely used lipid-lowering drug, is frequently released into water bodies via human excreta. Due to its resistance to natural light degradation, its prolonged accumulation in the environment may pose significant ecological risks. Semiconductor photocatalysis has gained increasing attention as an eco-friendly and versatile method for removing refractory pollutants. Among various photocatalysts, bismuth tungstate (Bi2WO6) has emerged as a promising photocatalyst due to its strong visible-light response and high chemical stability. However, its application remains limited by its energy band structure, low separation efficiency of photogenerated carriers, and small specific surface area. In this study, Bi2WO6 was utilized for the visible-light driven photocatalytic degradation of fluvastatin. The research investigates the influence of precursor pH during hydrothermal synthesis on the morphological structure and photoelectric properties of Bi2WO6. Additionally, reactive radicals and intermediates analyses were conducted to elucidate the degradation mechanism of fluvastatin. The morphology, crystal phase, optical absorption performance, specific surface area, electrochemical performance, and carrier separation ability of the synthesized Bi2WO6 photocatalyst were characterized using an electrochemical workstation and steady-state fluorescence spectroscopy. Its performance and stability were evaluated through degradation and cyclic experiments, and the effects of different pH conditions on photocatalytic efficiency were also examined. Additionally, active species analysis and intermediate product identification were employed to elucidate the degradation mechanism of fluvastatin. The results indicate that as the precursor pH shifts from acidic to neutral, the crystal growth of Bi2WO6 is disrupted, leading to the stacking of nanosheets. Under alkaline conditions, disordered octahedral phase polymers are formed. The optimal precursor pH was found to be 0.5, yielding an ordered, three-dimensional nanoflower morphology. Although variations in precursor pH did not significantly affect the light absorption capacity of Bi2WO6, increasing the pH resulted in a decrease in specific surface area and pore volume, from 57 m2·g–1 and 0.045 cm3·g–1 to 3.5 m2·g–1 and 0.002 cm3·g–1, respectively. Electrochemical experiments and steady-state fluorescence spectra further revealed that the efficiency of photogenerated carrier separation gradually decreases with increasing precursor pH. At pH 0.5, Bi2WO6 exhibited the highest photocatalytic performance, achieving 69.84% fluvastatin degradation after 120 min of illumination. Moreover, after four cycles of testing, the catalyst demonstrated stable performance, with the degradation rate remaining nearly unchanged. Free radical experiments demonstrated that h+ ions play the primary oxidative role in the degradation process, with ·OH and ·\begin{document}${O}_2^- $\end{document} radicals contributing as supplementary effects. These reactive species attack the C–C bonds in fluvastatin molecule, breaking them down into small cyclic organics, straight-chain organics, and hydroxylated derivatives, which are ultimately converted into CO2 and H2O.